2001
DOI: 10.1023/a:1011297326696
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our findings do not provide evidence that regular green tea consumption is related to reduced cancer risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 30 publications
3
56
1
Order By: Relevance
“…We identified 28 studies on the risk of bladder cancer and tea consumption between 1980 and March 2012 [11,12,13,14,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. After a closer examination, 10 studies were excluded due to lack of information [35,36,37,38,39,40,41,42,43,44].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 28 studies on the risk of bladder cancer and tea consumption between 1980 and March 2012 [11,12,13,14,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. After a closer examination, 10 studies were excluded due to lack of information [35,36,37,38,39,40,41,42,43,44].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, another study was abandoned for duplicated data [34]. Finally, a total of 17 studies including 8,225 cases were involved in our analysis [11,12,13,14,21,22,23,24,25,26,27,28,29,30,31,32,33]. Among the chosen studies, 4 were cohort studies [21,22,23,26] and 13 were case-control ones [11,12,13,14,24,25,27,28,29,30,31,32,33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leong et al (2008) used the C3(1)/SV40 mouse model to evaluate the chemopreventive effects of green tea on human breast cancer, which showed that the administration of 0.5% polyphenol in drinking water significantly suppressed the development of tumor growth by 40% compared to tap water-fed animals. The association between green tea intake and breast cancer risk has been investigated in five prospective cohort studies conducted in Japan (Nagano et al, 2001;Suzuki et al, 2004;Iwasaki et al, 2010), Singapore (Yuan et al, 2005;Inoue et al, 2008), and Shanghai, China (Dai et al, 2010). These prospective cohort studies with a total of 2067 breast cancer cases, show that there is no association between the breast cancer risk and green tea drinking.…”
Section: Prevention Of Cancermentioning
confidence: 99%